2019
DOI: 10.1002/14651858.cd012894.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve psychosocial well-being in female BRCA-mutation carriers following risk-reducing surgery

Abstract: Interventions to improve psychosocial well-being in female BRCA-mutation carriers following risk-reducing surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 112 publications
0
14
0
1
Order By: Relevance
“…Studies have revealed that mindfulness-based interventions have a positive impact on symptom burden and psychological outcomes in patients with cancer (Rouleau et al, 2015 ). Specifically speaking, when patients suffer from destructive effects resulting from both external and internal stressors, the MBSR program initiates psychological adjustment to trigger positive psychological sources (positive reappraisal) (Jeffers et al, 2019 ), which may greatly dilute the destructive effects of stressors (Galante et al, 2021 ) and then restore patient's psychosomatic balance. As a result, patients' health outcomes would be significantly improved.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that mindfulness-based interventions have a positive impact on symptom burden and psychological outcomes in patients with cancer (Rouleau et al, 2015 ). Specifically speaking, when patients suffer from destructive effects resulting from both external and internal stressors, the MBSR program initiates psychological adjustment to trigger positive psychological sources (positive reappraisal) (Jeffers et al, 2019 ), which may greatly dilute the destructive effects of stressors (Galante et al, 2021 ) and then restore patient's psychosomatic balance. As a result, patients' health outcomes would be significantly improved.…”
Section: Discussionmentioning
confidence: 99%
“…Multimodal screening with Transvaginal Ultrasound (TVUS) and CA-125 versus TVUS alone or without screening, showed that multimodal screening is effective in detecting early-stage cancer; after a median of 11 years of follow-up, with no reduction in mortality; screening for familial ovarian cancer; women with an estimated lifetime risk of ovarian cancer not less than 10% were screened for ovarian cancer by CA-125 testing every 4 months; the Ovarian Cancer Risk Algorithm (ROCA) used to interpret the results and TVUS (annually or within 2 months if the ROCA score is abnormal) [25]; the sensitivity, Positive Predictive Value (PPV), and Negative Predictive Value (NPV) for screening for ovarian cancer at 1 year were 94.7, 10.8, and 100%, respectively. For women screened at risk of familial / genetic ovarian cancer, ROCA every 3 months had better early stage sensitivity with high specificity and a low but possibly acceptable PPV compared to CA125> 35 U / ml every 6 / every 12 months, warranting a larger cohort assessment [64].…”
Section: Risk Managementmentioning
confidence: 98%
“…[4][5][6] Prophylactic surgery has been shown to be clinically effective and cost-effective for many high-risk groups, but come with mental, emotional, and physical health risks. [7][8][9][10][11][12] Prior studies have consistently identified underuse of and delayed prophylactic surgery utilization as impediments to genomic medicine's population impact on cancer outcomes. [13][14][15] Underuse of BSO and total hysterectomy are of specific concern because effective ovarian and endometrial cancer surveillance methods do not exist and these cancers are often diagnosed at a stage where treatment options are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Except for chemoprevention and colonoscopy, these prophylactic surgeries are the only risk‐management approaches that reduce personal cancer risk 4–6 . Prophylactic surgery has been shown to be clinically effective and cost‐effective for many high‐risk groups, but come with mental, emotional, and physical health risks 7–12 . Prior studies have consistently identified underuse of and delayed prophylactic surgery utilization as impediments to genomic medicine's population impact on cancer outcomes 13–15 .…”
Section: Introductionmentioning
confidence: 99%